2012
DOI: 10.1103/physrevc.86.057304
|View full text |Cite
|
Sign up to set email alerts
|

Nonaxial-octupoleY32correlations inN=150isotones from multidimensional constrained covariant density functional theories

Abstract: The non-axial reflection-asymmetric β32 shape in some transfermium nuclei with N = 150, namely 246 Cm, 248 Cf, 250 Fm, and 252 No are investigated with multidimensional constrained covariant density functional theories. By using the density-dependent point coupling covariant density functional theory with the parameter set DD-PC1 in the particle-hole channel, it is found that, for the ground states of 248 Cf and 250 Fm, the non-axial octupole deformation parameter β32 > 0.03 and the energy gain due to the β… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 55 publications
(66 reference statements)
3
66
0
Order By: Relevance
“…With these configuration assignments for the two pairs of nearly degenerate bands, calculations based on a combination of the microscopic multidimensionally-constrained covariant density functional theory (MDC-CDFT) [48][49][50] and the triaxial particle rotor model (TPRM) [51][52][53][54] have been performed. The MDC-CDFT calculations with the PC-PK1 parameterization [55] show that the deformation parameters are ðβ 2 ; γÞ ¼ ð0.32; 15.1°Þ and (0.23, 26.3°) for the πg 9=2 ⊗ νg 9=2 and πf 5=2 ⊗ νg 9=2 configurations, respectively.…”
mentioning
confidence: 99%
“…With these configuration assignments for the two pairs of nearly degenerate bands, calculations based on a combination of the microscopic multidimensionally-constrained covariant density functional theory (MDC-CDFT) [48][49][50] and the triaxial particle rotor model (TPRM) [51][52][53][54] have been performed. The MDC-CDFT calculations with the PC-PK1 parameterization [55] show that the deformation parameters are ðβ 2 ; γÞ ¼ ð0.32; 15.1°Þ and (0.23, 26.3°) for the πg 9=2 ⊗ νg 9=2 and πf 5=2 ⊗ νg 9=2 configurations, respectively.…”
mentioning
confidence: 99%
“…We can also expect, the appearance of additional low-lying 0 − and 2 − bands, as a negative parity doublets to the β and γ-vibrational bands. Note that the alternative explanation of the appearance of the low-lying 2 − bands in actinides is based on the concept of tetrahedral deformation [17,18].…”
Section: Excitation Spectra Of Actinidesmentioning
confidence: 99%
“…A self-consistent and microscopic study of Y 32 effects in these N = 150 isotones was carried out in Ref. [81] and it was found that, for ground states of 248 Cf and 250 Fm, β 32 > 0.03 and the energy gain due to the β 32 distortion is more than 300 keV.…”
Section: Introductionmentioning
confidence: 99%